Eigen Frequencies of a Vertical Axis Wind Turbine Tower Made of Laminated Wood and the Effect upon Attaching Guy Wires. Issue 3 (June 2014) - Möllerström, Erik; Ottermo, Fredric; Hylander, Jonny; Bernhoff, Hans
Eigen frequencies of a vertical axis wind turbine tower made out of laminated wood which are both bolted to the ground and supported by guy wires are studied and compared. Using beam theory, an analytical model taking the guy wires into account for calculating the first mode eigen frequency of the tower has been derived. The analytical model is then evaluated by comparing with FEM-simulations and measurements performed on the actual tower. The model is found to be reasonably accurate keeping in mind that the estimated masses and second moments of area are somewhat rough. Furthermore the model can be used to give an indication of the magnitude of change in eigen frequency when modifying a tower or guy wire property.